No stone unturned: The epidemiology and outcomes of paediatric urolithiasis in Manchester, United Kingdom. Issue 3 (June 2020) - Robinson, Cal; Shenoy, Mohan; Hennayake, Supul
Summary: Background: The epidemiology and risk factors for paediatric urolithiasis (UL) in developed countries are evolving, with increasing rates of metabolic stone-formers. In the United Kingdom (UK), only a single London cohort has been studied in the past three decades. Regional disease patterns across the UK remain unknown. UL has been associated with an increased risk of chronic kidney disease in adults, but long-term paediatric outcomes remain poorly understood. Methods: We assessed the epidemiology of paediatric UL by defining the demographics, incidence, aetiology, recurrence rates and outcomes at tertiary nephro-urology centres in Greater Manchester. Health records of 177 consecutive paediatric urology referrals (0–18 years) for UL between 2002 and 2015 were retrospectively included for observational analysis. Metabolic screening was performed in 105 children. Results: The incidence of paediatric urology referrals for UL was 1.77/100, 000 person-years, increasing annually by 13.6%. Mean patient age was 8.2 years and the male:female ratio was 1.3:1. The upper urinary tract was involved in more than 90% of cases and 45% of children presented with multiple calculi. Metabolic abnormalities were identified in 52% of children screened: hypercalciuria (64%), hyperoxaluria (18%) and cystinuria (11%) were the most common. Significant family history was predictive of metabolic abnormalities (OR 4.9:1, 95% CI 1.4–17.0). 30% of children had infective stones, which were more common in children less than 6 years. Ultrasound was found to be 90% sensitive for UL detection. Dimercaptosuccinic acid (DMSA) imaging identified renal scarring in 33 of the 55 children tested (60%). Recurrence was observed in 18% of children over mean 6.4 year follow-up and was more common in metabolic stone-formers. Spontaneous passage was observed in 83% of stones ≤ 5 mm, 69% between 5 and 10 mm and only one calculi > 10 mm. Conclusions: The incidence of paediatric urology referrals for UL is rising in North West England. Metabolic abnormalities were detected in half of the children tested, justifying comprehensive screening. Recurrence is common following paediatric UL, reinforcing the need for stone prevention strategies. The majority of calculi less than 10 mm were found to pass spontaneously with supportive measures, which favours an initial observation period over surgical intervention for small calculi. UL was associated with renal scarring in the analysed population and therefore, children with UL require long-term assessment of blood pressure and proteinuria. Figure – Aetiological classification: by age. (A) Males (n = 58). (B) Females (n = 47).